Analisis Korelasi antara Pengangguran, Kemiskinan, dan Ketimpangan Pendapatan di Provinsi Sumatera Barat - Widia May Wulan Sari; Dewi Zaini Putri (Universitas Negeri Padang, 2022)
The purpose of this study is to explore the correlation between unemployment,poverty, and income inequality in West Sumatra. We use secondary data whichis in the form of time series with a period of 2000 to 2020, where in collectingdata, documentation techniques and literature studies are applied which areobtained from related institutions. The variables of this study include:unemployment, poverty and income inequality. The research method used isPearson Product Moment correlation, using normality test, correlation test andt test. The results show that: (1) unemployment has a positive and significantcorrelation with poverty in West Sumatra. (2) income inequality is negativelyand significantly correlated with poverty in West Sumatra. (3) unemployment isnegatively and significantly correlated with income inequality in West Sumatra.Structural Equation Modeling (SEM).